The Policy Implementation Analysis of Inflation Control in Sukabumi Municipality: Implementation of Municipal Decree Number 188.45/39-Ekbang Dan KD/ 2018 In Sukabumi Municipality - Rahminingrum, Anita; Rahmawati, Ike; Sugiharto, Sugiharto (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
Controlling inflation requires cross-agency cooperation and coordination between the government at both the central and regional levels and Bank Indonesia. Strengthening coordination in order to achieve low and stable inflation is the background for the formation of the Regional Inflation Control Team (TPID). TPID was first formed in Sukabumi City in 2011. Efforts to achieve TPID's goals were achieved through implementing an inflation control roadmap with the 4K key strategy, namely price affordability, supply availability, smooth distribution and effective communication. The conformity of inflation achievement with the target is one measure of the success of implementing inflation control policies. In the last fourteen years, six periods of Sukabumi City's actual inflation were within Bank Indonesia's inflation target, while in the other eight years actual inflation was below or above the target. as many as 6 periods, this research uses a descriptive method with a qualitative approach. Data collection techniques through interviews, observation and documentation studies. The research objects were members of the Sukabumi City TPID and West Java Province TPID resource persons. The implementation of the inflation control policy in Sukabumi City is running effectively because the policy standards and targets have been integrated into the development planning program and won an award for the best performance in controlling regional inflation in 2021. The implementing human resources show good quality and are very supportive. However, supporting facilities and infrastructure still need special attention. The TPID implementing organization is a bureaucracy that complies with the legality of existing laws. Communication between related organizations is running well according to communication progress. The current social, economic and political environment is favorable. Effectiveness will increase if it is supported by a budget, infrastructure facilities, increased insight of the parties involved, and a complete inflation control intervention program. Policies need to continue to be updated to be adaptive to dynamic developments in economic phenomena.